Changes in pectin characteristics of jujube fruits cv "Dongzao" and "Jinsixiaozao" during cold storage. Issue 7 (19th June 2021) - Wang, Yingrui; Ding, Shenghua; Chen, Fei; Xiao, Guangjian; Fu, Xincheng; Wang, Rongrong
Abstract : Abstract: Softening is one of the main factors affecting market value and consumer preferences for jujubes, and it was closely related to the modification and depolymerization of pectin. Changes in characteristics of three pectins (water‐soluble pectin (WSP), sodium carbonate‐soluble pectin (SSP) and chelate‐soluble pectin (CSP)), including their contents, degree of methylesterification (DM), neutral sugar compositions, the molecular weight ( M w ) distributions and nanostructures, from two jujube fruits cv Dongzao (DZ) and Jinsixiaozao (JS) during cold storage were assessed. The results showed that variation in pectin characteristics during cold storage was similar between DZ and JS. The reduction of firmness corresponded to a conversion of water‐insoluble pectin to WSP during cold storage. DM of WSP presented an increase trend in the late storage. Rhamnose (Rha), arabinose (Ara) and glucose (Glc) were the crucial compositions in three pectins, and most neutral sugar compositions in three pectins first increased and then decreased during cold storage. Changes in the ratio of (galactose (Gal)+Ara)/Rha and Ara/Gal represented that the branch chains of rhamnogalacturonan‐I in three pectins depolymerized after storage. The high M w in WSP and SSP of jujubes were solubilized and extensively depolymerized into pectin with lower M w after storage. AFM images showed an increase in short chains and branch structures of three pectins after storage. Overall, three pectins in DZ and JS depolymerized and solubilized during cold storage. WSP and SSP were more contributed to the softening of jujubes compared to CSP, and they played the critical role for regulating the softening of jujube fruits during cold storage. Practical Application: Softening is one of the main factors affecting market value and consumer preferences for jujubes, and it was closely related to the modification and depolymerization of pectin. Changes in characteristics of three pectins (WSP, SSP, CSP), including their contents, degree of methylesterification, neutral sugar compositions, the molecular weight distributions and nanostructures, from two jujube fruits cv Dongzao (DZ) and Jinsixiaozao (JS) during cold storage were assessed. Three pectins in DZ and JS depolymerized and solubilized during cold storage. WSP and SSP were more contributed to the softening of jujubes compared to CSP, and they played the critical role for regulating the softening of jujube fruits during cold storage. This study would elucidate the mechanism of jujube softening and help to regulate the postharvest quality during cold storage.